MODERN SELF-ALIENATION SPECIFICITY AND HISTORIC PERSPECTIVES PROBLEM - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article clarifies modern features of self-alienation of a man in political, moral, ethical, cultural, everyday-utilitarian aspects of life, as well as measures of readiness of the mass consciousness to meet the challenges of historical perspectives.